2007
DOI: 10.1080/13651820701504157
|View full text |Cite
|
Sign up to set email alerts
|

Nonalcoholic fatty pancreas disease

Abstract: These data suggest that obese mice have 1) heavier pancreata, 2) more pancreatic fat, especially triglycerides and FFAs, and 3) increased cytokines. We conclude that obesity leads to nonalcoholic fatty pancreatic disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
132
0
10

Year Published

2009
2009
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 174 publications
(146 citation statements)
references
References 44 publications
(63 reference statements)
4
132
0
10
Order By: Relevance
“…In this model, circulating adiponectin inversely mirrored the severity of AP. We have also observed that pancreata of obese mice contain an increased volume of fat, a different composition of fat, and increased basal level of proinflammatory cytokines interleukin-1b (IL-1b), and interleukin-6 (IL-6) relative to wild-type lean mice [5,6].…”
Section: Introductionmentioning
confidence: 88%
See 1 more Smart Citation
“…In this model, circulating adiponectin inversely mirrored the severity of AP. We have also observed that pancreata of obese mice contain an increased volume of fat, a different composition of fat, and increased basal level of proinflammatory cytokines interleukin-1b (IL-1b), and interleukin-6 (IL-6) relative to wild-type lean mice [5,6].…”
Section: Introductionmentioning
confidence: 88%
“…Obesity is associated with fatty infiltration in the heart, kidney, liver, and pancreas. This situation leads to a generalized proinflammatory milieu and subsequent organ dysfunction [3][4][5][6]. Acute pancreatitis (AP) represents a substantial clinical problem, accounting for over 240,000 hospital admission annually in the United States, at a cost of over $2.3 billion [7].…”
Section: Introductionmentioning
confidence: 99%
“…Fatty pancreas is associated with decreased β -cell function and impaired insulin secretion in small case series ( 12,13 ). Pro-infl ammatory cytokines such as tumor necrosis factor-alpha and interleukin-1 β are increased in the pancreas of obese mice ( 14 ). Such animals also have an abnormal pancreatic islet size ( 15 ).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, some experimental work has begun to address the mechanisms by which fat contributes to pancreatic disease. Recent data from our laboratory showed that obese Lep ob mice have an elevated pancreatic fat content and increased baseline levels of the proinflammatory cytokines TNF-␣ and IL-1 ␤ relative to lean wild-type mice [3] . In addition, obese leptin-deficient Lep ob and obese hyperleptinemic Lep db mice develop more severe pancreatitis than lean mice when subjected to cerulein hyperstimulation [16] .…”
Section: Introductionmentioning
confidence: 99%